Hubungan Dukungan Suami terhadap Sikap Ibu untuk Imunisasi Bayi di Desa Denai Sarang Burung Kecamatan Pantai Labu Tahun 2023 - Siti Anum Ginting; Plora Novita Febrina Sinaga (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Immunity to one disease in a child does not mean immunity to other diseases. Immunization is a way to increase a person's immunity, such as when a child is actively fighting a disease in his body. The aim of this study was to determine the relationship between husband's support and mothers' attitudes towards immunization of newborns in Denai Sarang Burung Pantai Labu Village in 2023. In this study a cross-sectional technique was used. Cross sectional techniques are used to study the dynamics of the relationship between risk and impact variables by accessing, viewing or collecting data at once. Total population 45. Results of research on the relationship between husband's support and mother's attitude. Implementation of infant immunization in Denai Sarang Burung Village.